2007
DOI: 10.1542/peds.2005-2857
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function at 11 Years of Age in Preterm-Born Children With and Without Fetal Brain Sparing

Abstract: Children with fetal brain sparing do not demonstrate a different development of their visual functioning at late school age. However, an abnormal cerebral ultrasound in the neonatal period is associated with impaired visual function in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
1
21
1
3
Order By: Relevance
“…During the study period a total of 430 scans were performed on 115 IUGR fetuses (median 3, range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The proportion of cases with two, three or more than three examinations was 43.5, 34.8 and 21.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…During the study period a total of 430 scans were performed on 115 IUGR fetuses (median 3, range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The proportion of cases with two, three or more than three examinations was 43.5, 34.8 and 21.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…3 Numerous large-scale follow-up studies, such as INCAP 4 and ALSPAC, 5 have showed that IUGR is associated with significant neurodevelopmental impairment across a range of outcomes. 1,[6][7][8][9][10][11] The phenotypic characteristics of IUGR relate to the nature, duration, and severity of the factors affecting the developing fetus, the interactions between these factors, and maternal health and nutritional status. [12][13][14] The long-term effects of such diverse intrauterine insults are expected to result in heterogeneous outcomes, 15 and affect specific elements of development differently.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm delivery is associated with an increased risk for neurocognitive, 22,23 sensory, 10 and behavioural 24 impairments. Although preterm delivery and IUGR often cooccur, 25 the manner in which IUGR and timing of delivery interact in augmenting the risk of impaired neurodevelopment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…8). Furthermore, it has also been extensively reported that the prediction of adverse outcome is improved using umbilical and cerebral parameters in a combined ratio, [68][69][70][71][72][73][74] with sensitivities of about 70% 64,69,75 ( Fig. 9).…”
Section: Iugr Versus Normal-sgamentioning
confidence: 99%
“…Recently, studies in the same cohort confirmed that brain sparing was associated with impaired visual function and visual motor capabilities at 11 years of age. 71,72 In consequence, further evidence is required before recommending its use as an isolated surveillance tool.…”
Section: %mentioning
confidence: 99%